Pengalaman Praktis Anggota GIBEI dalam Memahami Mekanisme Investasi Syariah - Syahru Ramadlan Alghofar; Peni Haryanti (Journal of Economic and Business Advancement, 2025)
This study aims to explore the practical experiences of members of the Galeri Investasi Bursa Efek Indonesia (GIBEI) in understanding sharia-compliant investment mechanisms. The background of this research is the rapid development of the Islamic capital market in Indonesia that is not always followed by adequate literacy among university students as prospective investors, especially regarding the differences between conventional and sharia investment instruments. Using a qualitative descriptive approach, this study focuses on GIBEI members at an Islamic university who are actively involved in training, simulations, and real trading of sharia stocks. Data were collected through in-depth interviews with GIBEI members, mentors, and capital market educators, participatory observation in training and simulation sessions, and documentation of learning modules and trading records). Data analysis was conducted through stages of data reduction, data display, and conclusion drawing with source triangulation to ensure validity.  The findings indicate that GIBEI members have strengthened their understanding of Islamic investment through an integration of theoretical learning and practical experience, fostering prudence and the ability to critically assess financial instruments based on principles of Sharia compliance. This experience has shaped them into young investors who are more competent and uphold strong integrity in applying Islamic values within their investment practices